Major depressive disorder in detention officers - Santos,Sheila Nascimento (2021)
ABSTRACT OBJECTIVE To identify factors associated with major depressive disorder (MDD) in detention officers. METHODS This cross-sectional study included all detention officers from the largest prison complex in the state of Bahia, Brazil. A self-reported questionnaire collected sociodemographic, occupational and health data. The outcome variable – MDD – was evaluated by the Patient Health Questionnaire-9 (PHQ-9) and classified by the cut-off point ≥ 10 method and the algorithm method. The association measure used was the prevalence ratio (PR). Following Cox multivariate regression, the variables were divided into two blocks: sociodemographic characteristics and work, in that order. Only variables with adjusted PR (PRadj) ≥ 1.30 were selected to compose the final models. RESULTS The MDD prevalence by the cut-off point ≥ 10 (simple) and algorithm method in the 401 officers investigated was 18.8% and 9.3%, respectively. MDD prevalence by cut-off point ≥ 10 was higher in female officers (PRadj = 2.77), who suffered threat from factions (PRadj = 2.05), did not report institutional training for the position (PRadj = 1.38), stated that the environment and working conditions interfered in their physical health (PRadj = 3.51) and performed stress-generating activities (PRadj in increasing gradient). MDD prevalence by the algorithm method was higher in female agents (PRadj = 3.45), with tertiary education (PRadj = 1.71), who stated that the environment and working conditions interfered in their physical health (PRadj = 6.33), suffered threat from factions (PRadj = 2.14), did not report institutional training (PRadj = 1.50) and have frequent contact with inmates at work (PRadj = 1.48). CONCLUSION The high MDD prevalence in these detention officers was associated with sociodemographic factors and, especially, aspects of their work.